Effectiveness of hypertensive gymnastics physical exercise on lowering blood pressure in hypertensive patients - Maria Kurni Menga; Yuriatson Yuriatson; Idawati Binti Ambo Hamsa (Edukasi Ilmiah Indonesia, 2025)
Introduction: Hypertension is a primary global health concern often referred to as a